Decanoic acid-enriched ketogenic diet in refractory epilepsy - Shin, Hui Jin; Ryu, Seonae; Lee, NaRae; Lee, Eunjoo; Ko, Ara; Kang, Hoon-Chul; Lee, Joon Soo; Kim, Se Hee; Kim, Heung Dong (Frontiers in Neurology, 2025)
ObjectiveTo assess the anti-seizure efficacy and safety of a C10-enriched medium-chain triglyceride (MCT) ketogenic diet (KD) compared with the classic KD in pediatric patients with refractory epilepsy.MethodsThis 16-week, open-label, randomized, controlled, crossover pilot study was conducted at Severance Children’s Hospital, Seoul, South Korea, between August 2022 and September 2023. Fifteen pediatric patients with refractory epilepsy were enrolled and received classic KD and C10-enriched KD for 8 weeks each. The study compared seizure reduction rate, tolerability, and safety of the two diets.ResultsFifteen patients were enrolled. Patients were divided into 2 groups depending on the type of KD initiated. Ten patients completed the trial. Initial treatment with the C10-enriched KD resulted in seizure reduction in all five patients, with two becoming seizure-free. Initial treatment with classic KD was effective in two out of five patients. Upon crossover, those initially on C10-enriched KD maintained their seizure reduction, while patients initially on the classic KD showed additional seizure reduction when switched to C10-enriched KD. Adverse effects included transient hypoglycemia, metabolic acidosis, hypercalciuria, and gastrointestinal symptoms, all of which were manageable.DiscussionThe C10-enriched KD demonstrated comparable efficacy and tolerability to the classic KD, offering a promising option for patients with refractory epilepsy who do not respond adequately to the classic KD alone. This study, the first to directly compare a C10-enriched KD with a classic KD, highlights the potential synergistic effects of decanoic acid.